Effect of Doping Ce Ions on Morphology and Photocatalytic Activity of CuO Nanostructures. Issue 9 (7th August 2019) - Chen, Yajie; Tan, Haiwen; Wu, Xiaoqing; Sun, Qimeng; Wang, Dagui; Wang, Yongqian
Abstract: By one‐step hydrothermal method, pure and Ce‐doped CuO nanostructures (NSs) are successfully synthesized. In this work, C4 H6 CuO4 ·H2 O and Ce(NO3 )3 ·6H2 O are used as the precursor and the dopant. The results of X‐ray diffraction and energy dispersive spectroscopy demonstrate that small portions of Ce ions are incorporated into the crystal lattice of CuO NSs and substitute Cu ions with the formation of a tiny impurity (Cu2 O). Field emission scanning electron microscopy images display that the nanoellipsoid morphology of pure CuO transforms to an apparently rough surface with larger sizes of the morphology by doping with Ce element. Compared to pure CuO NSs, the UV–vis absorption of Ce‐doped CuO NSs is remarkably enhanced, which exhibits a strong ability of light absorption both in the 200–380 nm and in the visible region (380–800 nm). The measured band‐gaps of pure and Ce‐doped CuO NSs with different amounts of Ce ions are 2.07 and 1.93, 2.03, 2.02 eV, respectively. The photocatalytic test shows that the photocatalytic activity of Ce‐doped CuO NSs is eminently better than for pure CuO NSs, with the photodegradation of methylene blue solution rising up to 90.04%. Abstract : By one‐step hydrothermal method, pure and Ce‐doped CuO nanostructures are successfully synthesized. The structural and morphological information of samples is characterized by X‐ray diffraction and field emission scanning electron microscopy. The chemical composition is obtained by energy dispersive spectroscopy. The optical and photocatalytic performance of samples is tested by UV–vis and photodegradation test.